Fine‐needle aspiration cytology for parotid lesions, can we avoid surgery?. (21st December 2017) - Shkedy, Y.; Alkan, U.; Mizrachi, A.; Shochat, T.; Dimitstein, O.; Morgenstern, S.; Shpitzer, T.; Bachar, G.
Abstract : Objective: Salivary gland neoplasms are rare tumours, with most arising in the parotid gland. Fine‐needle aspiration cytology (FNAC) is a common method for preoperative evaluation of parotid masses, although its usefulness is controversial. This study was designed to evaluate the accuracy of FNAC in a large cohort of patients, with emphasis on diagnosis of benign tumours and especially Warthin tumour which can be managed conservatively. Study Design: Retrospective case series with chart review. Setting: Tertiary medical centre. Subjects and Methods: From 1991 to 2014, all patients 18 or older with both preoperative FNAC and postoperative pathology report were included. Patients with a history of head and neck malignancy or chronic sialoadenitis and patients who had undergone prior oncological treatment were excluded. Results: 470 patients were available for analysis. Overall accuracy was 82.6%. Positive predictive value (PPV) varied between 88.6% and 94.3% for pleomorphic adenoma and 77.1%‐100% for Warthin tumour, with values varying depending on different characteristics of patients (eg age, smoking status). For pathologically proven malignant tumours, the FNAC diagnosis was benign or non‐diagnostic in 26% of the cases. Conclusion: Fine‐needle aspiration cytology has limited utility in confirming a benign diagnosis of a parotid mass for most patients, although for some subpopulations, the PPV may be high enough to defer surgery.